MRI correlates of clinical disability and hand-motor performance in multiple sclerosis phenotypes. (July 2021) - Cordani, Claudio; Hidalgo de la Cruz, Milagros; Meani, Alessandro; Valsasina, Paola; Esposito, Federica; Pagani, Elisabetta; Filippi, Massimo; Rocca, Maria A
Background: Hand-motor impairment affects a large proportion of multiple sclerosis (MS) patients; however, its substrates are still poorly understood. Objectives: To investigate the association between global disability, hand-motor impairment, and alterations in motor-relevant structural and functional magnetic resonance imaging (MRI) networks in MS patients with different clinical phenotypes. Methods: One hundred thirty-four healthy controls (HC) and 364 MS patients (250 relapsing-remitting MS (RRMS) and 114 progressive MS (PMS)) underwent Expanded Disability Status Scale (EDSS) rating, nine-hole peg test (9HPT), and electronic finger tapping rate (EFTR). Structural and resting state (RS) functional MRI scans were used to perform a source-based morphometry on gray matter (GM) components, to analyze white matter (WM) tract diffusivity indices and to perform a RS seed-based approach from the primary motor cortex involved in hand movement (hand-motor cortex). Random forest analyses identified the predictors of clinical impairment. Result: In RRMS, global measures of atrophy and lesions together with measures of structural damage of motor-related regions predicted EDSS (out-of-bag (OOB)- R 2 = 0.19, p -range = <0.001–0.04), z9HPT (right: OOB- R 2 = 0.14; left: OOB- R 2 = 0.24, p -range = <0.001–0.03). No RS functional connectivity (FC) abnormalities were identified in RRMS models. In PMS, cerebellar and sensorimotor regions atrophy, cerebellar peduncles integrity and increased RS FC between left hand-motor cortex and right inferior frontal gyrus predicted EDSS (OBB- R 2 = 0.16, p -range = 0.02–0.04). Conclusion: In RRMS, only measures of structural damage contribute to explain motor impairment, whereas both structural and functional MRI measures predict clinical disability in PMS. A multiparametric MRI approach could be relevant to investigate hand-motor impairment in different MS phenotypes.